The Influence of Asphalt Concentration Addition in Hot Mix to the Characteristics of Laston (AC-WC) - Dwi Idarto; Ezra Hartarto Pongtuluran; Totok Sulistyo (Civil Engineering Dept, Balikpapan State Polytechnics, 2002)
A runway infrastructure is the main access of aircraft in making movements, the quality of the runway is expected to provide comfort and safety. Generally, the type of asphalt used in runway pavement is PEN and PG asphalt, PEN asphalt is used in the center line located at the middle of the runway and PG in the treshold which is at the starting point of the aircraft tire at take off or during the exhalation of the aircraft, the main consideration in determining the quality of the asphalt mixture. The marshall test method itself with the addition of asphalt levels by wet, where from the Marshall test obtained results in the form of Marshall components, namely stability, Cavity in the mixture(Void In The Compacted Mixture / VIM),Air cavity filled with asphalt(Voids Filled with Bitumen / VFB),Cavities between aggregates (Void in the Mineral Aggregat / VMA),and Marshall Results / Marshall Quotient ( MQ ), Based on the results of the study of 3 variants of asphalt levels of 5%, 6%, 7% using PEN and PG asphalt produced optimum asphalt levels of 7% with a stability value of 3030 kN / mm, Value(flow)of 4.0 mm, For cavity values in concrete asphalt VIM value of 2.71%, VMA value of 16.87%, and value of VFB of 83.97% for variations of PEN asphalt and for PG asphalt variants resulting in optimum asphalt content of 6% with stability value of 3640 kN/mm, Value(flow)of 3.2 mm, For cavity values in concrete asphalt VIM value of 3.32%, VMA value of 15.8%, and value from VFB of 78.39%. In asphalt concrete mixtures with 3 variations in asphalt levels, flow values tend to increase, while stability, QM, density, and air cavity tend to decrease compared to normal asphalt concrete Overall in the addition of mixtures, to lower the pavement and flexibility to be low. Large asphalt rate 7% for Pen with a value of 3234 kN / mm, and for 6%. for Pg with a value of 3640 kN / mm.